EVALUASI PROGRAM PELATIHAN 6S PADA KARYAWAN BAGIAN PRODUKSI DI PT X - Yuliana Lestari (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
Many companies give a training to employees in order to increase their performance. With the increase of employee’s performance can improve the companies growth. However, there’s one important thing that lot of companies ignore it, that is an evaluation of training. Usually companies only focus on what training programs will be given to the employees without follow up to evaluate whether the training effective or not. With this evaluation companies can understand what the strengths and the weaknesses of training that has been done. The purpose of this research is to explain the production employee’s opinion about 6S training, application of 6S after training, the difference of production target achievement before and after training and the reduction of spoilage product after 6S.Key words: 6S training, evaluation of training (reaction, behavior/ performance, organizational results level)